Helping traumatized people survive: a psychoanalytic intervention in a contaminated site - Guglielmucci, Fanny; Franzoi, Isabella G.; Barbasio, Chiara P.; Borgogno, Francesca V.; Granieri, Antonella (Frontiers in Psychology, 2014)
Psychoanalytic literature on extreme traumatization usually distinguishes between natural catastrophes and man-made catastrophes. While the first ones are usually sensed as nature’s ferocity, fate or God’s will, the second ones are experienced as a volountary and violent attack aimed at disrupting other human beings. In this paper we focus on man-made disasters caused by a profit-driven logic. When traumatization is due to irresponsible actions perpetrated by the owners of the major economic resource of a community, it deeply affects the identity of the group, entailing the loss of basic trust and lively parts of the Self. In such a situation, where the whole community is severely traumatized, psychoanalytic group therapy seems to be the most suitable setting: it allows to place the traumatic event into a historical framework and the creation of multiple narratives of somato-psychic suffering. Trust and faith are two crucial factors in the encounter with patients lacking a sense of vitality. The working through of each one through the group field is an essential forerunner to the construction of a recovered sense of faith and reliability, that precedes the onset of a true new-beginning.